A novel brain targeted plasma exosomes enhance the neuroprotective efficacy of edaravone in ischemic stroke - Lin Guo; Junlu Pan; Fang Li; Liang Zhao; Yijie Shi (IET Nanobiotechnology)
Abstract Ischemic stroke is often involved in the excessive production of reactive oxygen species (ROS), which aggravate ischemic injury. Edaravone (EDV) as an efficient free radical scavenger has demonstrated the effective neuroprotective effects in the therapy of ischemic stroke. Although EDV promotes ischemic recovery by inhibiting the generation of ROS, its poor safety and bioavailability limit its clinical applications. Herein, we developed plasma exosomes (EXO) containing EDV (EXO + EDV) for improving short‐term functional and histological outcomes for stroke treatment. The results showed that EXO + EDV improved brain targeting based on the transferrin–transferrin receptor interaction, and the safety and bioavailability of EDV were also significantly increased. Furthermore, compared with EDV, EXO + EDV significantly rescued ischemic damage in brain tissue by reducing infarct area and improving neurological performance in the acute stage of stroke (first 7 days).